Introduction to clinical research training - Dubai.(March-September 2020) - Mustafa, Huda; Kamel, Walaa (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
It is well known that there is a great need for research training programs in the scientific community of the MENA region. The increasing number of clinical trials conducted in the region mandates that all involved personnel undergo the necessary training to work on increasingly complex studies, ensuring adequate quality in clinical trials and adherence to international guidelines. The Introduction to Clinical Research Training program ICRT conducted in Dubai by Harvard Medical School is considered one of the leading clinical research training programs in the region with great benefits and adjustable limitations.
Keywords: Dubai; education; Harvard; Middle East; research; trials